Inductive-coupling system for abdominal aortic aneurysms monitoring based on pressure sensing - Sepúlveda, A. T. (2010)
Permanently implanted sensors with continuous monitoring of pressure for cardiovasc lar applications are particularly attractive as they provide additional opportunities for better therapies and enhanced quality of life. In Abdominal Aortic Aneurysms (AAAs), where stent-grafts are frequen ly used for treatment, are exemplary applications for this type of device. This paper introduces a new carbon nanotube (CNT)-based flexible capacitive sensor along with two different reading based on inductive-coupling. The fabrica for the flexible sensor and the main characteristics of the reading systems are presented, as well as tion results and preliminary experimental results of CNT-PDMS elements. Electrical conductivity of PDMS membranes with embedded aligned CNTs is 10 S/m, in the direction perpendicular to the CNT axis.